The antimicrobial activity of magnetron sputtered Ag doped aluminum oxide coatings in vitro - Safonov, V.; Donkov, N.; Zykova, A.; Avramov, L.; Dudin, S.; Yakovin, S.; Naidenski, H.; Avramova, I. (Вопросы атомной науки и техники, 2019)
The effect of Ag-doped aluminium oxide coatings deposited by magnetron sputtering method on the antibacterial efficiency against Gram-positive, Gram-negative bacteria and fungi has been investigated. The structure and composition of coatings were analysed by means of scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), photoelectron spectroscopy (XPS) methods. The results of the study suggest that Ag-doped aluminium oxide coatings demonstrate improved bactericidal effect and have great potential in various medical applications.